Ruptured Sinus of Valsalva Aneurysm (KYAMC Journal, 2020)
Sinus of Valsalva Aneurysms are extremely rare cardiac anomalies.The sinus of Valsalva aneurysm (SVA) is a small dilatation caused by a separation between the aortic media and annulus fibrosus. Its may be either acquired or congenital. The right coronary sinus is most frequently affected. The most common complication being rupture.We present the case of a 12-year old girl with ruptured non-coronary sinus of valsalva aneurysm associated with ventricular septal defect , mitral regurgitation grade II and severe pulmonary hypertension. Echocardiography is sufficient to diagnose SVA, its complications, repercussions, and surgical options. SVA, even if asymptomatic, has potential risks of expansion,rupture, cardiac failure, endocarditis, embolism and sudden death. This justifies surgical correction, with a low mortality rate in both the short- and long-term.KYAMC Journal Vol. 10, No.-4, January 2020, Page 211-213